1996
DOI: 10.1128/jb.178.1.321-324.1996
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of iclR, the gene encoding the repressor of the glyoxylate bypass operon

Abstract: The aceBAK operon was partially induced by a multicopy plasmid which carried the promoter region of the gene which encodes its repressor, iclR. Gel shift and DNase I analyses demonstrated that IclR binds to its own promoter. Disruption of iclR increased the expression of an iclR::lacZ operon fusion. Although aceBAK and iclR are both regulated by IclR, aceBAK expression responds to the carbon source, while expression of iclR does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 26 publications
2
60
0
Order By: Relevance
“…However, the promoter region upstream of the TS1 site was similar to that of the E. coli ace operon, and contained a similar palindrome structure to that of the ace operon, to which its specific repressor protein, IclR, binds ( Fig. 5a) (Gui et al, 1996 ;Negre et al, 1992). The promoter region of icdI encoding acetate-inducible IDH-I isozyme of C. maris was also reported to resemble that of the E. coli ace operon (Ishii et al, 1993 ;Suzuki et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the promoter region upstream of the TS1 site was similar to that of the E. coli ace operon, and contained a similar palindrome structure to that of the ace operon, to which its specific repressor protein, IclR, binds ( Fig. 5a) (Gui et al, 1996 ;Negre et al, 1992). The promoter region of icdI encoding acetate-inducible IDH-I isozyme of C. maris was also reported to resemble that of the E. coli ace operon (Ishii et al, 1993 ;Suzuki et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…4a) Inverted arrows indicate palindromic repeats. In aceB, this sequence is the IclR repressor binding site (Gui et al, 1996). The putative k35 and k10 promoter elements and the putative transcriptional start points (j1) are indicated by bold and boxed letters, respectively.…”
Section: Analysis Of 5h-terminal Region Of the C Maris Icl Mrnamentioning
confidence: 99%
“…E. coli IclR also forms a dimer and regulates both the aceBAK operon and its own expression. [30][31][32] Furuta et al 20 previously reported that the region between 100 and 274 a.a. of IclR is involved in dimerization and that this region can be replaced with other functional homodimerization domains (Figure 1). To design a high-throughput screening system targeting the WalR RR, we constructed a chimeric repressor gene consisting of sequences encoding the 100 amino-terminal amino acid residues of IclR that constitute the DNA-binding domain (N100) fused to the walR, arcA or ompR RR genes (Figure 2a).…”
Section: High-throughput Screening Of Inhibitors Targeting Walrmentioning
confidence: 99%
“…Further studies revealed that IclR autologously represses transcription of iclR itself (Gui et al, 1996), and two different modes of repression have been proposed for repression of aceBAK transcription by IclR (Yamamoto & Ishihama, 2003).…”
Section: Introductionmentioning
confidence: 99%